Optimizing Marketing Strategies and Porter’s Five Forces Analysis to Enhance Visitor Engagement - Habibur Rahman; Fazila Akrami; Mary Gregory; Kristi Kõiv; Sveta Berdibayeva; Garth Lipps; Deborah Yazhini Charles; Shupikai Zebron (Economy and Finance Enthusiastic, 2025)
Sentul Adventure is a tourism destination known for its rural charm and natural beauty, offering attractions such as river tubing, camping, outbound activities, and rice fields. However, since May 2018, the destination has seen a decline in visitor numbers due to increased competition and the availability of substitute products in the area. To address this, research was conducted to propose alternative strategies to increase visitor numbers. The study utilized the 7P marketing mix to analyze internal conditions and Porter’s Five Forces to assess external factors. Additionally, the Competitive Profile Matrix (CPM) was used to evaluate Sentul Adventure's position relative to its competitors, with further weighting through the Analytical Hierarchy Process (AHP). The SWOT matrix, Grand Strategy Matrix, and Internal-External (IE) Matrix were then employed to match strategies, followed by the use of the Quantitative Strategic Planning Matrix (QSPM) to select and analyze the recommended alternative strategies. The results revealed that the marketing mix approach identified 32 factors, while Porter’s Five Forces highlighted 19 factors. Sentul Adventure achieved the highest score among competitors in the CPM analysis. In the Grand Strategy Matrix, the destination was placed in a quadrant indicating strong market growth but weak competitive positioning. The IE Matrix placed Sentul Adventure in a quadrant that suggests a need for strategic improvements. Ultimately, the study identified market penetration, market development, and product development as the most suitable strategies, with market penetration emerging as the top alternative after analysis through the QSPM.